Analysis of the Effectiveness of Visual Language and Narrative in Conveying Value Propositions in Pitching Decks - Rahardja, Untung; Budiarto, Mukti; Lutfiyah, Konita; Wahyudi, Otniel Feliks Putra; Azz, Istajib Kulla Himmy; Azizah, Nur; Julianingsih, Dwi (International Transactions on Artificial Intelligence, 2025)
A pitching deck is a strategic communication medium that plays a crucial role in delivering value propositions to prospective investors in a concise yet persuasive manner. The effectiveness of message delivery through a pitching deck is highly determined by the quality of the visual language and narrative employed. This study aims to analyze how visual elements such as color, typography, infographics, and iconography interact synergistically with the narrative structure to convey complex business values more intuitively and emotionally. The methodology used is a literature study with a thematic analysis approach of scientific sources published within the last five years. The findings indicate that consistent visual integration and structured narrative not only enhance audience understanding but also strengthen memory retention and emotional engagement with the presented business ideas. Specifically, this combined approach opens significant opportunities for the development of intelligent models capable of adaptively evaluating and recommending pitching deck designs with personalization. The implications of this study point to the need for communication decision support systems that focus not only on business content but also on how data driven technologies and algorithms can improve the quality of visual narrative elements as persuasive tools in the startup and investment world.